Pemodelan Konveksi Panas Pada Fluida Statis dan Dinamis Dalam Bentuk Persamaan Diferensial Orde 1 - Eka Finanti Simamora; Nurcahaya Br Zandroto; Putri Tarigan; Vico Putra Sidauruk; Fevi Rahmawati Suwanto (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This article discusses the importance of understanding heat convection in fluids in the context of physics and engineering. Using first order Simple Differential Equations (PDS), we can analyze the temperature distribution in a fluid over time and space in high detail. PDS allows modeling heat convection by considering parameters such as temperature differences and fluid flow velocity. Numerical methods are used to complete the PDS computationally, while data collection techniques through literature studies provide an in-depth understanding of relevant theories and previous findings. With the application of PDS and numerical methods, we can better understand and predict heat transfer in fluids, which has wide applications in engineering, biology, and physics. In conclusion, this article provides a comprehensive insight into the use of PDS in the analysis of heat convection in static and dynamic fluids, with a focus on mathematical and computational approaches to better understand this phenomenon.